The Opioid System in Temporal Lobe Epilepsy: Functional Role and Therapeutic Potential - Burtscher, Johannes; Schwarzer, Christoph (Frontiers in Molecular Neuroscience, 2017)
Temporal lobe epilepsy is considered to be one of the most common and severe forms of focal epilepsies. Patients often develop cognitive deficits and emotional blunting along the progression of the disease. The high incidence of resistance to antiepileptic drugs and a frequent lack of admissibility to surgery poses an unmet medical challenge. In the urgent quest of novel treatment strategies, neuropeptides are interesting candidates, however, their therapeutic potential has not yet been exploited. This review focuses on the functional role of the endogenous opioid system with respect to temporal lobe epilepsy, specifically in the hippocampus. The role of dynorphins and kappa opioid receptors (KOPr) as modulators of neuronal excitability is well understood: both the reduced release of glutamate as well of postsynaptic hyperpolarization were shown in glutamatergic neurons. In line with this, low levels of dynorphin in humans and mice increase the risk of epilepsy development. The role of enkephalins is not understood so well. On one hand, some agonists of the delta opioid receptors (DOPr) display pro-convulsant properties probably through inhibition of GABAergic interneurons. On the other hand, enkephalins play a neuro-protective role under hypoxic or anoxic conditions, most probably through positive effects on mitochondrial function. Despite the supposed absence of endorphins in the hippocampus, exogenous activation of the mu opioid receptors (MOPr) induces pro-convulsant effects. Recently-expanded knowledge of the complex ways opioid receptors ligands elicit their effects (including biased agonism, mixed binding, and opioid receptor heteromers), opens up exciting new therapeutic potentials with regards to seizures and epilepsy. Potential adverse side effects of KOPr agonists may be minimized through functional selectivity. Preclinical data suggest a high potential of such compounds to control seizures, with a strong predictive validity towards human patients. The discovery of DOPr-agonists without proconvulsant potential stimulates the research on the therapeutic use of neuroprotective potential of the enkephalin / DOPr system.